2021
DOI: 10.1038/s41598-020-79194-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic signatures of the evolution of defence against its natural enemies in the poisonous and medicinal plant Datura stramonium (Solanaceae)

Abstract: Tropane alkaloids and terpenoids are widely used in the medicine and pharmaceutic industry and evolved as chemical defenses against herbivores and pathogens in the annual herb Datura stramonium (Solanaceae). Here, we present the first draft genomes of two plants from contrasting environments of D. stramonium. Using these de novo assemblies, along with other previously published genomes from 11 Solanaceae species, we carried out comparative genomic analyses to provide insights on the genome evolution of D. stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 106 publications
7
31
0
Order By: Relevance
“…Beyond pollination, these G-type lectin receptor-like kinases (LecRLKs) are known to be involved in other aspects of signalling, in particular, mediating responses to insect attacks (Gilardoni et al, 2011). Plant-insect interactions have emerged as major drivers of genome evolution, especially in Solanaceae (De-la-Cruz et al, 2021;Fan et al, 2020), and our findings from Iochroma suggest that LecRLKs merit additional investigation as mediators of these interactions (Sun et al, 2020).…”
Section: Gene Family Evolution In Iochromamentioning
confidence: 85%
“…Beyond pollination, these G-type lectin receptor-like kinases (LecRLKs) are known to be involved in other aspects of signalling, in particular, mediating responses to insect attacks (Gilardoni et al, 2011). Plant-insect interactions have emerged as major drivers of genome evolution, especially in Solanaceae (De-la-Cruz et al, 2021;Fan et al, 2020), and our findings from Iochroma suggest that LecRLKs merit additional investigation as mediators of these interactions (Sun et al, 2020).…”
Section: Gene Family Evolution In Iochromamentioning
confidence: 85%
“…Four Datura and three Nicotiana transcriptomes were used for phylogenetic and gene family evolution analyses. Since we encountered logistic issues downloading other Solanaceae transcriptomes (e.g., Solanum transcriptomes), we decided to use these three Nicotiana species for gene family construction (see De-la-Cruz et al, 2021). Thus, protein-coding genes and CDS from the three Nicotiana transcriptomes were sourced from the Sol Genomics Network 2 [N. tomentosiformis (Sierro et al, 2013), N. sylvestris (Sierro et al, 2013), and N. attenuata (Xu et al, 2017)].…”
Section: Ortholog Identification and Phylogenetic Inferencementioning
confidence: 99%
“…Genomic studies have been central to investigating the evolution and diversification of ecologically and economically relevant plant species, such as the Solanaceae family (Soltis and Soltis, 2021). Several species of this plant family have been subjected to metabolomic and genomic studies on specialized secondary metabolites, such as terpenoids, tropane alkaloids, glycoalkaloids, and phenolics, implicated as defenses against natural enemies (Friedman, 2002(Friedman, , 2006Cheng et al, 2007;Sierro et al, 2014;Akyol et al, 2016;Chowański et al, 2016;Xu et al, 2017;De-la-Cruz et al, 2021). However, this is not the case for nonmodel plant species in the Solanaceae family -such as Datura species -where few genomic studies examining the processes and candidate genes that underlie evolutionary diversification have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Construction of orthogroups, gene families, was performed according to De-la-Cruz et al (2021) using Orthofinder v2.3.3 (Emms & Kelly, 2015Emms & Kelly, 2019). The phylogenetic tree inference was accomplished using the program BEAST with the pair-wise deletion option, and reliability of the obtained phylogenetic tree was tested by bootstrapping with 1,000,000 MKKM chains.…”
Section: Identification Of Orthogroups and Inference Of Phylogenetic Tree Of Tpa And Tpssmentioning
confidence: 99%
“…In recent years it has been reported that the responses of specialized metabolites are grouped into several multigenic families. Therefore, we aim to elucidate the evolutionary process of two gene families, TAs (Tropane alkaloids) and TPSs (terpenes synthases) (Karunanithi & Zerbe, 2019;De-la-Cruz et al, 2021). Studies conducted in Solanaceae have found rapid responses to biotic and abiotic stimuli, in a matter of minutes, of genes involved in the synthesis of specialized metabolites (atropine, scopolamine, VOCs) (Brille, Loreto & Baccelli, 2019).…”
Section: Introductionmentioning
confidence: 99%